Caracterização de cultivares de feijão para pré- de grãos desidratados de cozimento rápido e processamento industrial - Schoeninger, Vanderleia (2015)
Currently an alternative that meets the demands of the modern consumer is the industrial processing. Due to the necessity of scientific materials about beans industrial processing in the national literature, then the objective in the first stage of this work (Paper 1) was prepare a review about this topic. Were presented some concepts and details of the industrial processing, unit operations and quality parameters evaluated in canned beans. In sequence (Paper 2) were presented the results of the study that evaluated the adaptability of eight bean cultivars for industrial processing. Cultivars evaluated were by commercial Carioca class: BRS Perola, BRS Estilo, BRS Ametista e BRS Notável and also the Black class: IPR Uirapuru, BRS Campeiro, BRS Esteio and BRS Esplendor. First the physical parameters of the grains were evaluated: water content, measurement of the size, roundness, weight of 100 seeds, density, bulk density, apparent moisture ratio and color components. Then the beans were processed at an industry of canning, using cans with a capacity of 420 g, in which the samples were put without the use of soaking. For sauce was used water at a temperature of 75°C and the cooking process and sterilization was performed in a rotary retort. The quality parameters were evaluated in canned beans: total, net and drained weight, headspace, damage index, color, soluble solids and total solids in the sauce, texture, acidity and pH. Data were submitted to multivariate analysis: Principal Components and Hierarchical Clustering. As a result it was found that the Carioca class BRS Estilo differs from others due to low drained weight that contributed to the increase of total solids in the broth, with low hardness values, not adapting to the type of process used in this experiment. In Black class were observed similar quality characteristics between cultivars BRS Esplendor and IPR Uirapuru, and between BRS Campeiro and BRS Esteio, especially this last one by having smaller index of damaged grains after processing. Lastly, in the last work (Paper 3) was presented information about a different option of product by beans, the quick cooking dehydrated, pointing details of the processing and the performance of Brazilian bean varieties, as well as the technological quality of the final product. In the processing of quick-cooking dried beans was used a Central Composite Design (CCD) with two factors. The first factor was cultivar, evaluating BRS Pérola, BRS Madrepérola, BRS Estilo and IAPAR 81. The second factor was concentration of NaHCO3 used in soaking operation followed by drying of the beans. Were evaluated the parameters: cooking time, damage index and color difference in the processed product. It was found that the effects on these quality parameters are dependent upon the cultivar factor, because BRS Estilo and BRS Madrepérola stood out due to reduced cooking time and color difference when compared to BRS Pérola and IAPAR 81. For BRS Estilo cultivar the increased of NaHCO3 concentration in the soaking reduced significantly the cooking time, with lower rates of damage when compared to BRS Madrepérola. Finally, the information in this work intends to contribute with future research on this topic and therefore increase the bean consumption, whether in the form of an innovative product like the quick cooking dehydrated or as canned beans.